Pengabdian Kepada Masyarakat: Perencanaan Lahan Desa Mekarwangi Menjadi Bangunan dan Ruang Publik Beridentitas Lokal - Khamdevi, Muhammar (LPPM Universitas Flores, 2024)
Mekarwangi Village does not currently have enough public space and buildings. Meanwhile, Mekarwangi Village is fast expanding as a result of the increase in formal housing in the Cisauk area, necessitating the construction of a public space and building before the village's land runs out. There is a 2,250-square-meter plot of land held by the community that is available for work. So, on this land, a public building and space will be developed to meet the needs of residents for public and educational space, the village government's need for space for various purposes, as well as representing local village identity. The outcomes of this community service take the shape of conceptual ideas for buildings and public spaces based on analysis of local needs, potential, and character.